Utilization of Waste Combustion Heat as an Alternative Renewable Electric Energy Source Based on Thermoelectric Generator - Yeni Rima Liana; Sulhadi Sulhadi; Mahardika Prasetya Aji (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2019)
Thermoelectric generator is one alternative energy source that is using a temperature difference system to produce electrical energy. This research study aims to utilize combustion heat waste using a thermoelectric generator as a source of renewable electricity. This research method uses the experimental method. The thermoelectric system was made using seven thermoelectric modules TEC1 - 12706 arranged in series by varying the combustion media in the form of Rice husk, Sengon sawdust (Albizia chinensis) and Teak sawdust (Tectona grandis). The test is done by measuring the output voltage, the temperature of the cold side and the hot side which are then analyzed to get the output power and generator efficiency. From the trial results it was found that the greater of the temperature difference, then the output voltage, output power and generator efficiency increase. Output voltage, output power and maximum efficiency of testing prototype thermoelectric generator that generated were 4.64 V, W 20.38 and 16.46 % with fuel Teak sawdust in the tenth minute when the temperature difference of 76.17 0C.©2019 JNSMR UIN Walisongo. All rights reserved.